EVALUATING OUTCOMES OF CHILDHOOD OBESITY MANAGEMENT: A 2-YEAR FOLLOW-UP STUDY - Suji, Nur Izzati Ahmad; Supian, Aisyah Mardhiah; Jalaludin, Muhammad Yazid; Samingan, Nurshadia Binti; Leong, Annie; Ambak, Noor Azleen Binti; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Childhood obesity (CO) clinic has served as screening and intervention center. Weight management programs in children have not been fully established. This report is to understand the outcome after 2 years of follow-up in the same clinic. METHODOLOGY Children who were newly referred to the clinic from 2020–2023 (4 years) were identified. Patient demographic and anthropometric (weight, height, BMI, blood pressure and waist circumference) data at point 0 (first visit) and point 1 (2 years from the first clinic visit) were collected. RESULT A total of 78 new patients were included. Majority, 51 (65%) were males. A total of 27 (35%) did not come back for their second follow-up. Another 22 (28%) defaulted 2 years before. Only 29 (37%) completed follow-up for 2 years. At time point 0, the overall mean age was 12.1 ± 3.05 years with 11.96 ± 2.9 and 12.16 ± 3.07 for females and males, respectively. The mean height, weight and BMI were 143.6 ± 23.6 cm, 70.46 ± 22.75 kg and 30.3 ± 6.9 kg/m² for females and 150.66 ± 20.4 cm, 70.95 ± 23.39 kg and 30.0 ± 5.0 kg/m² for males. At time point 1, the mean age for females was 13.45 ± 4.1 years-old and 14.2 ± 3.1 for males. The mean height and weight were 150.0 ± 19.3 cm and 76.8 ± 21.5 kg for females and 163.4 ± 19.6 cm and 83.7 ± 26.1 kg for males. The mean BMI were 32.4 ± 5.59 kg/m² and 31.3 ± 6.1 kg/m² for females and males, respectively. Amongst those completed 2 years follow-up, 6/29 (20.6%) had weight loss and their mean weight and BMI losses were –6.8 kg and 2.745 kg/m². Amongst those who gained weight, the BMI gain was 2.165 kg/m². Six developed hypertension and 4 were diagnosed with pre-diabetes while under follow-up. CONCLUSION The expectation of weight loss while attending CO clinic may be overestimated. In the real-world data, the majority would fail to lose weight further and may develop other complications instead. Weight loss programs dedicated for children are needed to help these high-risk populations.